Optimization of lignocellulosic biomass-to-biofuel supply chains with mobile pelleting. (February 2019) - Albashabsheh, Nibal T.; Heier Stamm, Jessica L.
Highlights: Biomass-to-biofuel supply chain optimization model examines mobile pelleting. Model simultaneously accounts for multiple biomass feedstock types and baling forms. Mobile pelleting is not economically attractive under current parameter values. Modest changes in cost or distance parameters make mobile pelleting attractive. Mobile pelleting is more attractive when more machines are available. Abstract: Mobile pelleting machines (MPMs) provide an as-yet-unexplored opportunity to reduce logistic costs associated with biomass-to-biofuel supply chains. We develop an optimization model to minimize the overall cost of producing ethanol from lignocellulosic biomass. We present results from a case study that considers multiple biomass types (switchgrass and corn stover) and forms (round and rectangular bales) and the potential for mobile pelleting. Our analyses offer insight into conditions under which mobile densification is economically viable. Results indicate that MPM utilization is sensitive to changes in biomass densification costs, transportation distances, satellite storage location fixed cost, and the number of MPMs.